A Study on C-Exponential Mean Labeling of Graphs - Thamaraiselvi Baskaran; Rajasekaran Ganapathy (Journal of Mathematics)
A function h is mentioned as a C-exponential mean labeling of a graph GV,E that has s vertices and r edges if h:VG⟶1,2,3,⋯,r+1 is injective and the generated function h∗:EG⟶2,3,4,⋯,r+1 defined by h∗ab=1/ehbhb/haha1/hb−ha, for all ab∈EG, is bijective. A graph which recognizes a C-exponential mean labeling is defined as C-exponential mean graph. In the following study, we have studied the exponential meanness of the path, the graph triangular tree of Tn, CmPn, cartesian product of two paths Pm▫Pn, one-sided step graph of STn, double-sided step graph of 2ST2n, one-sided arrow graph of Ars, double-sided arrow graph of DArs, and subdivision of ladder graph SLt.